SATGAS GOTONG ROYONG PENCEGAHAN COVID 19 BERBASIS DESA ADAT SEBAGAI UPAYA PEMERINTAH PROVINSI BALI MEMUTUS RANTAI PENYEBARAN VIRUS COVID-19 - I Gusti Ayu Jatiana Manik Wedanti (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The establishment of the Satgas Gotong Royong Pencegahan Covid-19 or Covid-19 Mutual Assistance Officer Unit is a policy taken by the Governor of Bali Province in responding to the rate of spread of COVID-19 in the Bali Province area. This strategic step is a form of harmonization between the Government and its people in preventing the spread of COVID-19. Prevention through this Task Force is an Indigenous Village-based prevention which is seen as effective in preventing the spread of COVID-19 in the Bali Province area and there is a pararem that strengthens the Task Force in carrying out its duties. Using normative research and qualitative descriptive analysis, it can be concluded that the Task Force for Covid-19 Prevention is an implementation of the harmonization of the Bali Provincial Government with the Balinese customary law community in this case the Traditional Village to jointly prevent and break the chain of the spread of COVID-19.